Organic Collaborative Research Partnership Building: Researchers, Needle and Syringe Program Providers, and People Who Inject Drugs - Danielle Resiak (MDPI AG, 2021)
(1) Background: People who inject drugs (PWID) and needle and syringe program (NSP) providers increasingly partner with researchers to explore harm reduction best practice. However, a paucity of research exists regarding how best to engage PWID and community NSP providers to generate the evidence for sustainable harm reduction services. (2) Aim: This study reports on our use of an organic community research partnership-building approach between researchers, NSP providers, and PWID in Canberra ACT, Australia. (3) Method: Survey participants included both PWID (n = 70) and NSP providers (n = 26) across primary (n = 2), secondary (n = 7), and outreach (n = 1) services in Canberra ACT. Applying an organic partnership-building strategy, we engaged with partners and adapted approaches according to information gained in the process of implementation. (4) Results: We found engaging in relationship building around partner priority activities created mutual understanding and trust premised in authenticity of the evolving partnership. Our organic approach, which included a partner audit of the research tools for relevance, resulted in high acceptance and enrolment into the research by NSP providers and PWID. Finally, we observed strong social capital building utilizing an organic approach for the sustainability of the partnership. (5) Conclusions: The results of this study provide evidence for the benefits of organic collaborative research partnership building with NSP providers and PWID for authentic service program implementation. Our approach to research partnership building resulted in strong relationships built on shared goals and objectives, mutual gains, and complementary expertise. We propose the wider use of organic approaches to developing collaborative research partnerships with NSP providers and PWID to enhance consumer responsiveness towards service provision.